Exposure to Workplace Violence and Related Factors among Nurses Working in Hospitals Affiliated with Golestan University of Medical Sciences - Alireza Heidari; Sakine Beygom Kazemi; Mohammad Javad Kabir; Zahra Khatirnamani; Mohammad Mehdi Zargaran; Mansoureh Lotfi; Sajad Moeini; Zahra Sherkat Ardebili (Taṣvīr-i salāmat, 2023)
Background. Workplace violence in the healthcare system has become an important policymaking issue in recent years and is considered one of the most complex issues for the governmental system. Due to the lack of a similar study in Golestan province, this study was conducted to determine the level of exposure to workplace violence against nurses and the factors related to it. Methods. This cross-sectional study was conducted in hospitals affiliated with Golestan University of Medical Sciences in 2021 Where 293 nurses were included after random stratified sampling. The data collection tool was demographic and occupational variables as well as the workplace violence questionnaire and data analysis was done by descriptive statistics methods and Mann-Whitney, Spearman, Kruskal-Wallis, and Chi-square tests in SPSS-23 software at a significance level of 0.05. Results. The average age of the nurses participating in the study was 33.93 ± 7.16 years and their average work experience was 9.82 ± 6.32 years. Among the subjects, 82.6% were women and the rest were men. The prevalence of workplace violence was 86% in one year. Mental and physical violence with a frequency of 79.5% and 42.7%, respectively, had the highest occurrences. Also, 57.7% did not report any act of violence. In front of these acts of violence, the most reactions were inviting the attacker to calm down (42.3%), discussing the issue with colleagues (23.5%), and not taking any specific action (19.5%). There was a significant relationship between physical violence and gender (P-value=0.024) and department of hospital (P-value=0.003). Sexual violence was also significantly related to department of hospital (P-value=0.046). Also, there was a significant relationship between racial violence and gender (P-value=0.001), department of hospital (P-value=0.028), and work shift (P-value=0.005). Conclusion. According to the results, the prevalence of workplace violence was generally high in one year, but most of the nurses did not report any act of violence. Therefore, medical policymakers and hospital managers should consider improving nurses' communication skills, and security measures, training staff on anger management, and reducing nurses' workload.